Analysis of microcirculation in the wound healing process after carbon dioxide laser therapy of stomatitis prothetica hyperplastica fibrosa - Ryniewicz, Joanna; Ryniewicz, Wojciech; Loster, Jolanta; Rogala, Maciej; Loster , Bartłomiej (Journal of Stomatology, 2015)
Background. Within the oral cavity, the coexistence of injury, infection, and the activity of toxic agents from denture material can give rise to proliferative lesions of the mucous membrane. Most frequently, such proliferations are excised with the CO2 laser. Aim of the study. To model wound healing after laser therapy and to indicate the moment for introducing prosthetic treatment following excision of the pathological lesion. Materials and methods. The tests were conducted in a group of generally healthy patients with stomatitis diagnosed in the oral vestibule. Surgery was carried out with the CO2 laser. The examination procedure consisted of microcirculation measurements before, immediately after, and on days 1, 2, 3, 4, 7, 15, and 30 after the procedure with the use of the laser Doppler flowmeter. Results. Differences in the blood supply in particular measurement periods were reported. From the duration determined, it can be indicated that healing takes sixty days. Conclusions. 1. The tests allowed a description of the pattern of healing. 2. The analysis indicated the thirtieth day of healing as the proper moment to introduce prosthetic treatment.